Mycobacterium tuberculosis infection of domesticated Asian elephants, Thailand - Taweepoke Angkawanish (2018)
Four Asian elephants were confirmed to be infected with Mycobacterium tuberculosis by bacterial culture, other diagnostic procedures, and sequencing of 16S-23S rDNA internal transcribed spacer region, 16S rRNA, and gyrase B gene sequences. Genotyping showed that the infectious agents originated from 4 sources in Thailand. To identify infections, a combination of diagnostic assays is essential.